ACTR-63. PHASE I DOSE ESCALATION STUDY OF PROCASPASE ACTIVATING COMPOUND-1 (PAC-1) IN COMBINATION WITH TEMOZOLOMIDE IN PATIENTS WITH RECURRENT ANAPLASTIC ASTROCYTOMA OR GLIOBLASTOMA. (11th November 2019) - Holdhoff, Matthias; Nicholas, Martin; Peterson, Richard; Danciu, Oana; Maraka, Stefania; Hergenrother, Paul; Tarasow, Theodore; Dudek, Arkadiusz
Abstract: BACKGROUND: Procaspase activating compound -1 (PAC-1) is a small molecule that catalyzes conversion of procaspase-3 to caspase-3 which induces apoptosis in cancer cells. Glioblastoma (GBM) is among the tumors with high concentrations of procaspase-3 and low levels of caspase-3. PAC-1 crosses the blood brain barrier and has been shown to synergize with temozolomide (TMZ) in canine malignant glioma and meningioma that arise spontaneously. METHODS: This is a multicenter phase 1 dose-escalation study to assess the maximum tolerated dose (MTD) of PAC-1 administered days 1–21 in combination with TMZ days 8–12 at a dose of 150 mg/m2 of each 28 day cycle in subjects with recurrent anaplastic astrocytoma (AA) or GBM. A modified Fibonacci 3 + 3 design is used with up to 4 dose levels of PAC-1 (375, 500, 625 and 750 mg/day). Neurologic toxicity, including cognitive function, is closely monitored throughout the trial. INTERIM DATA: A total of 14 subjects have been enrolled to-date. Of these, 7 at dose level 1, PAC-1 375 mg/day (6 GBM, 1 AA; median age 58y, range 25–75) and 7 at dose level 2, PAC-1 500 mg/day (5 GBM, 2 AA; median age 51y, range 35–60). Best responses to-date were 2 subjects with a partial response and 2 with stable disease. Grade 3 (hepatotoxicity) and 4 (cerebral edema) was reported as possibly related to PAC-1 in 1 patient at dose level 1. The median number of cycles received was 4 (range, 1–12+) at dose level 1 and 2 (range, 1–3) at dose level 2. Enrollment to dose level 2 has been completed and data analysis is ongoing. Updated response and toxicity as well as pharmacokinetic data will be presented.